Bamenda Criminal Case No. 20 (Colonial Letters and the Contact of Knowledges, 1929)
This file contains colonial court minutes on Bamenda criminal case No. 20
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies